2013
DOI: 10.5402/2013/927453
|View full text |Cite
|
Sign up to set email alerts
|

ColombianAnopheles triannulatus(Diptera: Culicidae) Naturally Infected withPlasmodiumspp.

Abstract: The role of Anopheles triannulatus as a local vector has not yet been defined for malaria-endemic regions of Colombia. Therefore, the aim of this work was to detect An. triannulatus naturally infected with Plasmodium spp., as an approximation to determining its importance as malaria vector in the country. A total of 510 An. triannulatus were collected in six malaria-endemic localities of NW and SE Colombia from January 2009 to March 2011. In the NW, two specimens were naturally infected; one with Plasmodium vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 48 publications
(83 reference statements)
1
14
0
11
Order By: Relevance
“…However, as the infected specimen on this study was recollected in livestock corrals and the Plasmodium spp. infection was only PCR-detected in the midgut of the mosquito, no transmission to humans can be inferred from this data as formerly discussed by other authors (11). Consequently, no incrimination should be stated until this is complemented with epidemiological data.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…However, as the infected specimen on this study was recollected in livestock corrals and the Plasmodium spp. infection was only PCR-detected in the midgut of the mosquito, no transmission to humans can be inferred from this data as formerly discussed by other authors (11). Consequently, no incrimination should be stated until this is complemented with epidemiological data.…”
Section: Discussionsupporting
confidence: 50%
“…In seven of the nine locations sampled during March and May, 2015, A. nuneztovari mosquitoes were present except in El Rayo-TAZ (Antioquia) and San Francisco de Tauchigadó-MAT (Chocó). Similarly, other studies have found A. nuneztovari in some locations of Antioquia and Chocó (6,7,11,16,26). Interestingly, the last report of A. nuneztovari in Chocó dates from 2004 (26), which evidences the importance of continuously listing malaria vectors present in the different regions of Colombia and keeping updated information for vector control strategies.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In this study, An. calderoni was detected infected with P. falciparum by the first ELISA and nested PCR but could not be confirmed by the second ELISA [63]. Given the difficulties still encountered in the tests to determine parasite infected mosquitoes, this result is reported here according to recommendation of defining a positive infected mosquito with the result of at least two positive tests [63].…”
Section: Discussionmentioning
confidence: 87%